Steroid‐free maintenance immunosuppression using alemtuzumab in pediatric kidney transplantation: Long‐term longitudinal follow‐up. (23rd October 2021) - Jain, Ashokkumar; Daoud, Deborah; Kees‐Folts, Deborah; Freeman, Michael A.; Butt, Fauzia; Abendroth, Catherine S.; Shike, Hiroko; Kadry, Zakiyah
Abstract: Background: There is a scarcity of long‐term data on steroid‐free immunosuppression using alemtuzumab in pediatric kidney transplantation (KTx). This study examines long‐term outcomes with alemtuzumab without steroid maintenance therapy in pediatric KTx. Methods: From July 2005 to June 2015, 71 pediatric KTx recipients received alemtuzumab without steroid maintenance. They were followed from 4.1 to 14.1 years post KTx. Results: Patient survival : One child expired with a functioning graft from post‐transplant lymphoproliferative disorder (PTLD). Patient survival was 98.6%. Graft survival : Eighteen grafts were lost (16 from chronic rejection). Graft survival at 5 and 10 years was 92.3% and 61.3%, respectively. Rejection : Twenty‐three ( 32.4%) patients were free from T‐cell‐mediated rejection (TCMR), 16 (22.5%) had >3 episodes. Sixteen (22.5%) were treated for antibody‐mediated rejection (AMR). Infection : Twenty‐three children developed Epstein‐Barr virus (EBV), 5 developed cytomegalovirus (CMV), and 20 developed BK virus infection. Four (5.6%) developed PTLD. Twenty‐two (31.0%) required treatment for neutropenia. Growth parameters : Mean height and weight increased by 0.56 and 0.69 SDS (standard deviation score), respectively. Body mass index increased by 5.1 kg/m 2 at 10 years. Less than 40% required antihypertensive medications at all‐time points. Conclusion: Alemtuzumab, without corticosteroid maintenance, offers 98.6% patient survival at 14 years with five and 10‐year graft survival of 92.3% and 61.3%, respectively. TCMR and AMR requiring treatment were 67.4% and 22.5%, respectively. CMV, EBV, and BK viremia rates were 7.0%, 32.4%, and 28.2%, respectively. Thirty‐one percent were treated for neutropenia; 5.6% developed PTLD. There were improvements in growth parameters and blood pressure.